Islam Progresif dalam Gerakan Sosial Dawam Rahardjo (1942-2016) - Dafit, Ahmad (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2017)
The phenomenon of poverty and injustice that continues until now, making a lot of Muslim figures to think again about Islamic thought. The Indonesian Islamic figure, one of the serious discussions of this issue is M. Dawam Rahardjo—for instance, we called Dawam. Based on the problem, this study focuses on the concept of thinking and implementation of Progressive Islam Dawam by reviewing, analyze, and discussing his work with a historical sociological approach. This research is descriptive-analytical with the qualitative method which is reinforced through in-depth interview. The results show that Dawam’s thought is part of Progressive Islam. He accepted the reality of the modern world, such as pluralism, liberalism, and secularism, then embraced all three in the strengthening of religiosity in society. Dawam is one of the Islamic leaders who have contributed to social change. Implementation can be seen from various works that concern Islamic renewal and community empowerment. His attitude and behavior can be seen in the institutions he leads—LSAF (Lembaga Studi Agama dan Filsafat) and LP3ES (Lembaga Penelitian, Pendidikan dan Penerangan Ekonomi dan Sosial). His criticism of the unjust political-economic order, accompanied by various solutions offered. Dawam’s idea in stemming the economic system that harms small people is the concept of cooperative development. Dawam chose the path of civil society and avoided political pragmatism. According to him, the Islamic struggle in the political path only tends to exploit religion for sectarian interests.Fenomena kemiskinan dan ketidakadilan yang masih berlanjut hingga saat ini, membuat banyak tokoh muslim berpikir ulang mengenai pemikiran keislaman. Tokoh Islam Indonesia, salah satu yang serius membincang persoalan ini adalah M. Dawam Rahardjo—selanjutnya Dawam. Berdasarkan soal tersebut, kajian ini fokus pada konsep pemikiran dan implementasi Islam Progresif Dawam dengan menelaah, mengkaji, dan membahas karyanya dengan pendekatan historissosiologis. Penelitian ini bersifat deskriptif-analitis dengan metode kualitatif yang diperkuat melalui wawancara mendalam. Hasilnya menunjukkan bahwa pemikiran Dawam bagian dari Islam Progresif. Ia menerima kenyataan dunia modern, seperti pluralisme, liberalisme, dan sekularisme, kemudian merengkuh ketiganya dalam penguatan keberagamaan di masyarakat. Dawam adalah salah satu tokoh Islam  yang memiliki andil dalam perubahan sosial. Implementasinya bisa dilihat dari berbagai karya yang concern pada pembaharuan Islam dan pemberdayaan masyarakat. Sikap dan perilakunya, dapat dilihat dalam lembaga yang ia pimpin—LSAF (Lembaga Studi Agama dan Filsafat) dan LP3ES (Lembaga Penelitian, Pendidikan dan Penerangan Ekonomi dan Sosial). Kritiknya atas tatanan ekonomi politik yang tidak adil, diiringi dengan berbagai solusi yang ditawarkan. Gagasan Dawam dalam membendung sistem ekonomi yang merugikan rakyat kecil adalah konsep pembangunan koperasi. Dawam milih jalur civil society, dan menghindari pragmatisme politik. Menurutnya, perjuangan keislaman di jalur politik hanya cenderung mengeksploitasi agama untuk kepentingan sektarian.